Notes on environmental subsidiarity (Società e diritti, 2023)
The contribution aims to formulate some reflections on the peculiar application of the principle of subsidiarity in environmental matters, in relation to the evolution of public approaches to environmental protection and, especially, the potential of the circular economy.